2001
DOI: 10.1111/1467-9280.00356
|View full text |Cite
|
Sign up to set email alerts
|

Trace and Delay Eyeblink Conditioning: Contrasting Phenomena of Declarative and Nondeclarative Memory

Abstract: We tested the proposal that trace and delay eyeblink conditioning aref fundamentally different kinds of learning. Strings of one, two, three, or four trials with the conditioned stimulus (CS) alone and strings of one, two, three, or four trials with paired presentations of both the CS and the unconditioned stimulus (US) occurred in such a way that the probability of a US was independent of string length. Before each trial, participants predicted the likelihood of the US on the next trial. During both delay (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
101
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 21 publications
10
101
3
2
Order By: Relevance
“…In this respect, our results are clear cut. They clearly generalize the eye-blink results previously described by Perruchet (1985) and Clark et al (2001) to the domain of voluntary responses. Our results strengthen the conclusions of studies showing that RTs may follow the same general laws as classically conditioned reactions (Los & Heslenfeld, 2005;Los, Knol, & Boers, 2001;Los & Van Den Heuvel, 2001;Razran, 1936;Rexroad, 1936;Stephens, 1937).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this respect, our results are clear cut. They clearly generalize the eye-blink results previously described by Perruchet (1985) and Clark et al (2001) to the domain of voluntary responses. Our results strengthen the conclusions of studies showing that RTs may follow the same general laws as classically conditioned reactions (Los & Heslenfeld, 2005;Los, Knol, & Boers, 2001;Los & Van Den Heuvel, 2001;Razran, 1936;Rexroad, 1936;Stephens, 1937).…”
Section: Discussionsupporting
confidence: 89%
“…A promising strategy concerns the search for the conditions in which the expression of these processes is favored or hampered. In eyeblink conditioning, Clark et al (2001) reported that the dissociation between subjective expectancy and eyeblink responses disappeared and even turned into an association when the tone terminated before the onset of the air puff (a preparation known as "trace conditioning") instead of coterminating with E2 (a preparation known as "delay conditioning"). The reliability of this pattern of data has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Such a pattern was reported during eye-blink conditioning (37). We failed to find any significant trend in response slope.…”
Section: Discussionsupporting
confidence: 62%
“…Early evidence comes from lesion studies with experimental animals showing that acquisition of trace conditioning requires intact hippocampal formation (4,5) and medial prefrontal cortex (6), whereas delay conditioning can occur even with the entire forebrain removed (7,8). Later studies involving human subjects further validate the involvement of different brain circuits in these two conditioning variants and even suggest, more surprisingly, that conscious awareness might be a prerequisite for trace but not delay conditioning (9,10). It is then hypothesized that the participation of hippocampus and neocortex, as well as the associated higher cognitive function, is necessary in trace conditioning to maintain a representation of the CS or CS/US contingency so as to bridge the temporal gap (11,12).…”
mentioning
confidence: 99%